Carlos Seré on the launch of the Biosciences eastern and central Africa Hub - International Livestock Research Institute (International Livestock Research Institute, 2010)
Speaking at the launch of the Biosciences eastern and central Africa (BecA) ILRI Hub on 5 November 2010, ILRI Director General Carlos Seré welcomed the President of Kenya and other guests. He said that the BecA ILRI hub now enables scientists from research institutes and universities across Eastern and Central Africa to come to Nairobi and undertake critical research using the most advanced tools. He emphasized how the Hub plays a critical role in responding to the urgent needs of Africa to boost science capacity. BecA is about exploiting the common body of knowledge to leap frog the search for solutions, this is BecA’s unique contribution to Africa’s science endeavor.